Hubungan Anemia dan Penyakit Ibu Terhadap Kejadian Abortus - Romlah Romlah; Anjelina Puspita Sari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: One of the causes is abortion with a prevalence of 5%. This study aims to determine the relationship between anemia and maternal disease with the incidence of abortion. Method: This type of research uses observational analytic with a cross sectional design. The sampling technique is total sampling, with a total sample of 46 respondents. Data were taken by retrospective observation of respondents' medical records. The analysis technique uses the Chi-Square test. Results: Statistical test results show a significant relationship between anemia and abortion (pv=0.035), there is a significant relationship between maternal disease and abortion (pv=0.017) Conclusion: Maternal factors inherent in the mother such as hemoglobin status and maternal disease need to be monitored. This monitoring can be done when the mother visits ANC visits, therefore it is recommended that mothers continue to consume iron tablets during pregnancy as much as 90 tablets to meet hemoglobin needs, and also make regular ANC visits.